Necessidade hídrica e adubação potássica no cultivo da abobrinha em ambiente protegido - Aquino, Fernando Caio de Freitas (Universidade Federal Rural do Semi-Árido, 2019)
Zucchinicultivation in a protectedenvironment in thenortheastregionhaslittle data relatedtoevapotranspirativedemand, thereisalsolittle data regardingtheeffectofpotassiumfertilization. The presentstudyaimsto determine theproduction, evapotranspirationandinteractionwithpotassiumfertilization in thecultivationofthecourgette (Cucurbita pepo) variety “Girl Brazilian” in protectedenvironment. The researchwascarried out in a greenhouse, in themunicipalityof Mossoró-RN, usinganautomateddripirrigation system. The treatmentsconsistedoftheapplicationoffiveirrigationdepths (T) andtwo doses ofpotassium (P): 120% ofETc (evapotranspiration) withpotassium (T1P1), 120%ETcwithoutpotassium (T1P2), 100% ETcwithpotassium (T2P1), 100% ETcwithoutpotassium (T2P2), 80% ETcwithpotassium (T3P1), 80% ETcwithoutpotassium (T3P2), 60% ETcwithpotassium (T4P1), 60% ETcwithoutpotassium (T4P2), 40% ETcwithpotassium (T5P1) and 40% ETcwithoutpotassium (T5P2). The ETcwasdeterminedusingweighingmicro-lysimeters (SPL) andsoilmoistureby a constructedandcalibratedCapacitive sensor (SC). The LeafArea (AF) wasdeterminedandattheendofcultivationtheAverageFruitWeight per plant (PMF). The correlationcoefficientabove 99% for SPL and SC calibrationshowedtheefficiencyoftheweightsensorsused. ComparedtotheKcestimatedbythe FAO method (KcFAO), thecontrolKc T2 washigher in thefirstthreestagesofdevelopmentby 18%, 11.39% and 1.94% respectively, beingloweronly in thelastphase in 13,48%. T1 KcwashigherthanothertreatmentsbutalsohigherthanKcFAO. The highest PA in the final phaseswasobtainedwithtreatment T2, butthehighestproductivitywasobtainedwithtreatment T1. As for potassiumfertilization, the P2 doses obtainedhigher PMF in thetwosmallerirrigationdepht, while in theotherirrigationdephtthe P1 dose was more productive.
Monografia
Keywords: Cucurbita pepo; Coeficiente de cultivo; Potássio; Fertirrigação; Cucurbita pepo; Zucchini; Cultivationcoefficient; Potassium; Fertirrigacion; CIENCIAS AGRARIAS::AGRONOMIA